Proceedings of the Proceedings of the 1st Seminar and Workshop on Research Design, for Education, Social Science, Arts, and Hum 2019
DOI: 10.4108/eai.27-4-2019.2286840
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dates (Phoenix Dactylifera Linn) on Blood Glucose Levels in Type-2 Diabetes Mellitus Patients

Abstract: Type-2 diabetes mellitus (DM) burdens health care costs when complications occurred. Dates (Phoenix dactylifera Linn) contain almost complete nutrients, fiber and rich in antioxidants, which can control blood glucose levels. This study aimed to determine the effect of dates on blood glucose levels. This was the experimental study with Randomized Control Trial Pretest and Posttest. There were 36 outpatients of type-2 DM, divided into two groups, control and treatment. 50 grams of Lulu dates were given to the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…However, this systematic review only included five research studies; thus, a limited number of studies cannot confirm the significance of such results, as agreed by Mirghani [54]. In addition, a randomized control trial performed on type 2 diabetic patients showed that the daily intake of 50 g of Lulu dates synergically with standard oral antidiabetic drugs for two weeks had no alleviating effect on blood glucose levels compared to the control group [55]. Therefore, diabetic patients may need to consume dates consciously, and further studies regarding dates' hypoglycemic effects are needed to confirm such claims.…”
Section: Anti-hyperglycemic Effectsmentioning
confidence: 93%
“…However, this systematic review only included five research studies; thus, a limited number of studies cannot confirm the significance of such results, as agreed by Mirghani [54]. In addition, a randomized control trial performed on type 2 diabetic patients showed that the daily intake of 50 g of Lulu dates synergically with standard oral antidiabetic drugs for two weeks had no alleviating effect on blood glucose levels compared to the control group [55]. Therefore, diabetic patients may need to consume dates consciously, and further studies regarding dates' hypoglycemic effects are needed to confirm such claims.…”
Section: Anti-hyperglycemic Effectsmentioning
confidence: 93%
“…Diabetes patients who ate different date types had decreased glycemia, according to a meta-analysis in the current systematic review [85]. In a randomized controlled trial of type 2 diabetics, 50 g of Lulu dates given daily with regular oral antidiabetic medications for two weeks did not influence blood glucose levels [86].…”
Section: Discussionmentioning
confidence: 77%